1986
DOI: 10.1111/j.1365-2842.1986.tb00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentine hypersensitivity: effect of interactions between metal salts, fluoride and chlorhexidine on the uptake by dentine

Abstract: A large number of compounds may be applied to the teeth for preventive or therapeutic purposes, most notably in dentine hypersensitivity. The uptake of any one compound by tooth substances may clearly be affected by another to produce synergistic, additive or antagonistic effects. This study determined whether uptake interactions occurred between fluoride, chlorhexidine, strontium, tin and zinc. All compounds, in particular tin, showed considerable affinity for dentine. Fluoride reduced the uptake of zinc but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…42 Some studies have demonstrated decreased hydrodynamic fluid flow within the dentine tubules upon oxalate treatment, thus reducing pain sensations. 41,[43][44][45][46] Another study demonstrated that oxalates block dentinal fluid flow by forming precipitates within the dentine tubules. 47 However, a systematic review regarding the effectiveness of oxalates in the treatment of dentine hypersensitivity determined that that single treatments of oxalates had no effect on dentine hypersensitivity compared to placebos.…”
Section: Introductionmentioning
confidence: 98%
“…42 Some studies have demonstrated decreased hydrodynamic fluid flow within the dentine tubules upon oxalate treatment, thus reducing pain sensations. 41,[43][44][45][46] Another study demonstrated that oxalates block dentinal fluid flow by forming precipitates within the dentine tubules. 47 However, a systematic review regarding the effectiveness of oxalates in the treatment of dentine hypersensitivity determined that that single treatments of oxalates had no effect on dentine hypersensitivity compared to placebos.…”
Section: Introductionmentioning
confidence: 98%
“…This is interesting in that the additional agents included a zinc salt and zinc salts appear able to adhere to dentine and occlude tubules, although this precipitate is labile in water. 24 Importantly, within the main aim of the study, the data show that the addition of anti-plaque agents to the desensitising product had no adverse effect on the efficacy. Clearly, it would have been of interest to record plaque and gingivitis levels throughout the study.…”
Section: Discussionmentioning
confidence: 97%
“…There are many clinical trials concerning the efficacy of a number of ‘actives’ in the treatment of dentine hypersensitivity, albeit mostly with equivocal or contradictory findings (for reviews see 4, 70). There are, however, no studies in vivo that reveal what is actually occurring at the dentine surface following toothbrushing with various toothpastes.…”
Section: Toothpaste and Oral Harmmentioning
confidence: 99%
“…These latter products have artificial silica‐based abrasive systems with alternative detergents to the usual anionic agent (sodium lauryl sulphate), a detergent that appears to compete with silica for attachment to the dentine surface. Evidence for dentine hypersensitivity actives in toothpastes that block tubules is completely lacking, although experiments using ‘actives’ in solution, such as stannous salts, indicate that tubules can be blocked (4).…”
Section: Toothpaste and Oral Harmmentioning
confidence: 99%
See 1 more Smart Citation